On the margins: young men's mundane experiences of austerity in English coastal towns - McDowell, L; Bonner-Thompson, C; Harris, A (Taylor and Francis, 2020)
This paper explores the everyday experiences of young white working-class men living in coastal towns badly affected by austerity programmes implemented in the UK since 2010. The lives and aspirations of marginal young men seldom feature in studies of the effects of economic crisis and austerity. These men are positioned at the intersection of several rhetorical constructions with contradictory and ambivalent affects. They are expected, and still expect, to become wage earners and providers, largely through their own efforts and self- improvement. A rhetoric of social mobility disguises structural inequality, producing a false promise of hope or ‘cruel optimism’ about future prospects. Simultaneously, young working- class men, especially those without employment, typically are constructed as a threat to (middle class) society, difficult or dangerous, and authors of their own disadvantage. We explore how young men, without regular work and often lacking family support, talk about everyday experiences, social relationships, feelings and emotions and hopes for the future in coastal towns with a particular place in the national imaginary.